STUDY OF IN SITU STRESS RATIO IMPACTS AGAINST DISPLACEMENT AND INDUCED STRESS ALONG UNDERGROUND POWERHOUSE EXCAVATION USING FINITE ELEMENT METHOD - Mochamad Hambali (NIM : 12112076), Irham
Rock mass at depth is subjected to in situ stresses. Based on its orientation, in situ stresses are divided into vertical stress and horizontal stress (σv and σh). These stresses are not always possessing same value and will turn into induced stresses when tunnels are excavated. These things may cause underground instability if monitoring activities are not carried out. Besides observing physical condition of tunnels, underground stability can be predicted by using Finite Element Method. This research allows RS3 2.0 software to construct beam rock mass model with specific dimension such as 150x100x150 m. Rock mass model loaded with different in situ stresses ratio, which are 1:1:1; 1:1:2; and 1:2:1. In each model, a horseshoe shaped underground powerhouse also constructed with specific width of 18 m, height of 32 m and a final excavation length done until it reach 70 m. Displacement, induced stress, rock mass characteristic curve, and Safety Factor transformation are being observed at point 40 m for each tunnel advancing stage. From this experiment, largest roof displacement obtained from 1:1:1 and 1:2:1 ratio which is 1,15 cm and 1,13 cm. Meanwhile largest wall displacement obtained from 1:1:2 ratio which has value 5,4 cm. Induced stress from σv: σh1: σh2 = 1: 1: 1 ratio is safer on the roof, right wall, and the left wall of the underground powerhouse because it produces smallest σ1 compared to the other loading ratio. Excavation progress will affect the decrease of internal support pressure (Pi). Along with the decrease in Pi for each excavation progress, the displacement formed will also increase. The value of SF on the roof is stable because all ratios have SF>1 for each stage of excavation. Meanwhile, the wall that have SF<1 with the lowest SF value is 0,67 obtained from σv: σh1: σh2 = 1: 2: 1 ratio on the right wall.